Control and Automation, and Energy System Engineering International Conferences, CA and CES3 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon.; Adeli, Hojjat; Stoica, Adrian; Kang, Byeong-Ho.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book comprises selected papers of the International Conferences, CA and CES3 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of control and automation, and circuits, control, communication, electricity, electronics, energy, system, signal and simulation.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Software Engineering; Computation by Abstract Devices